48.0k views
0 votes
How to solve 2x= -x + 3 by graphing

1 Answer

6 votes

Answer:

x = 1

Explanation:

To find a solution to this by graphing, you would typically make a graph of the expression on the left, and another graph of the expression on the right. Where they intersect is the solution.

You would graph ...

  • y = 2x
  • y = -x +3

You're only interested in the x-value where these lines cross, x=1.

_____

Alternate method

Graph the difference of the left side and the right side:

y = (2x) -(-x +3)

and look for the value of x that makes y = 0. This, too, gives the solution x=1.

__

Of course, once you have the equation ...

0 = 3x -3

the solution is pretty obvious. (Divide by 3 to make it more obvious.)

How to solve 2x= -x + 3 by graphing-example-1
How to solve 2x= -x + 3 by graphing-example-2
User Karthikaruna
by
5.3k points